HUMAN, ARTIFICIAL INTELLIGENCE AND THE EXTIMACY OF THE UNCONSCIOUS - Perepelytsia, Oleh; Pavlenko, Oleksiy (The Journal of V. N. Karazin Kharkiv National University. Series "Theory of Culture and Philosophy of Science", 2025)
The The article examines the nature of the unconscious within the context of transforming relations between humans and technology, particularly artificial intelligence (AI). Special attention is devoted to the development of AI as a factor of subject decentration and as a condition for reconsidering the philosophical and ideological foundations of anthropocentrism. The study addresses radical changes in the sphere of communication, which becomes networked, distributed, and post-anthropic. The theoretical and methodological framework combines psychoanalytic, deconstructive and post-anthropological approaches, which make it possible to expand the understanding of the cognitive domain while also revealing the dimension of the unconscious. The article argues that technological tools such as large language models open access to a collective / extimate unconscious, expanding the space of expression while simultaneously removing individual responsibility for the generated meanings. Such technological mediation intensifies both the decentration and the (self-)alienation of the human, increasingly dispersed among others within digital flows. AI is interpreted as a fetishistic mechanism operating at the boundary between desire and the nihilistic devaluation of the (Other): technology is perceived as a useful instrument insofar as it satisfies specific desires and expectations, but is devalued once it fails to do so. The apocalyptic discourse surrounding AI uncovers the repressed layer of the social unconscious, indicating the erosion of the symbolic order. In this regard, the classical question “What can I know?”, interpreted through a Lacanian perspective, primarily reveals the structure of the unconscious in the age of AI and post-anthropic thinking. AI is thus understood not only as a instrument created by instrumental reason but also as a mechanism for exposing an unconscious that is no longer localized within the individual subject and therefore requires new methods of analysis – including philosophical ones. Consequently, the article outlines the possibility of rethinking the foundations of philosophy beyond traditional anthropocentrism, considering the emergence of a new (machinic) Other.